Materials chemistry : a multidisciplinary approach to innovative methods - Friedrich, Klaus, 1945-; Zaikov, G. E. (Gennadii Efremovich), 1935-; Haghi, A. K. (Apple Academic Press, 2016)
"This book focuses on important aspects of materials chemistry by providing an overview of the theoretical aspects of materials chemistry, by describing the characterization and analysis methods for materials, and by explaining physical transport mechanisms in various materials. Not only does this book summarize the classical theories of materials chemistry, but also it exhibits their engineering applications in response to the current key issues. The chapters provide practical equations, figures, and references, providing suitable complement to the text. This book is designed to provide important information for scientists and engineers on experimental research in materials chemistry using modern methods. The methods and instrumentation described represent modern analytical techniques useful to researchers, product development specialists, and quality control experts in polymer synthesis and manufacturing."--